รูปแบบการบริหารแบบมีส่วนร่วมเพื่อสนับสนุนการพัฒนาหลักสูตรบูรณาการการดํารงตนให้เป็นพลเมืองดีของโรงเรียนมัธยมศึกษา สังกัดสํานักงานคณะกรรมการการศึกษาขั้นพื้นฐาน - จันทรัตน์ พัชรา; อุทัยรัตน์ วีระวัฒน์ (Journal of Education Studies, Chulalongkorn University, 2019)
This research aimed to 1) study the composition of the participatory management supporting the development of integrated curriculum for good citizenship of secondary schools under Ofﬁce of Basic Education Commission, 2) specify the participatory management model supporting the development of integrated curriculum for good citizenship of secondary school’s students under Ofﬁce of Basic Education Commission, and 3) evaluate the participatory management model supporting the development of integrated curriculum for good citizen of secondary school’s students under the Ofﬁce of Basic Education Commission. Mixed-method research in both quantitative research and qualitative research were carried out to synthesize the composition of the participatory management supporting the development of integrated curriculum for good citizenship leading to being speciﬁed as the participatory management model supporting the development of integrated curriculum for good citizenship of secondary school’s students under Ofﬁce of Basic Education Commission. The results show that: 1) There were 3 major components of the participatory management supporting the development of integrated curriculum for good citizenship of secondary school’s students under Ofﬁce of Basic Education Commission which were: creating standards analyzing, promoting development and communication, and continuingthe living as good citizen. 22 minor components were also found. 2) The participatory management model supporting the development of integrated curriculum for good citizenship comprising main stress, objectives, processes, and methods were: standards analyzing creation, development and communication promotion, and good citizenship continuation under supervision of Ofﬁce of Basic Education Commission. 3) In overview, the participatory management model supporting the development of integrated curriculumfor good citizenship of secondary school’s students under Ofﬁce of Basic EducationCommission was model right, possible and useful in the most level as well as in componentby component consideration.